2010
DOI: 10.3116/16091833/11/1/1/2010
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emission of laser dye molecules in synthetic opals under conditions of low dielectric contrast

Abstract: Spontaneous emission of laser dye molecules (rhodamine 6G and pironin G) embedded into pores of synthetic opal photonic crystals is studied in the spectral region of 520-650 nm. It is ascertained that the emission spectra are greatly dependent on the photonic stop-band position and the spectral distribution of photon density of states. A dependence of spectral position of the emission band from the dielectric contrast is found. PACS:78.67-n , 78.55.Mb UDC: 535.361

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The same effect was observed by Moiseyenko et al 96 They found that the emission of a uorophore that was embedded into a synthetic opal was suppressed in the region of PBG and amplied at the "blue" edge of the photonic band.…”
Section: Band Gap and Band Edge Effects (Engineering At The Crystal L...supporting
confidence: 80%
“…The same effect was observed by Moiseyenko et al 96 They found that the emission of a uorophore that was embedded into a synthetic opal was suppressed in the region of PBG and amplied at the "blue" edge of the photonic band.…”
Section: Band Gap and Band Edge Effects (Engineering At The Crystal L...supporting
confidence: 80%
“…Luminescence spectra of laser dyes (rhodamine 6G and pironin G) are shown in Fig. 7 ( Moiseyenko et al, 2008Moiseyenko et al, , 2010. As seen from Fig.…”
Section: Laser Dyes Moleculesmentioning
confidence: 96%
“…Composed of the ordered close-packed silica particles with a diameter of several hundred nanometers, opals make it impossible for optical waves to propagate along some directions within a certain frequency range, the so-called photonic stopband [4]. Since the original opals are porous structures, substances with different refractive indices can be introduced into them, providing different optical contrast and thus controlling the photonic band parameters and, consequently, the spectrum of the outgoing radiation [5,6].…”
Section: Introductionmentioning
confidence: 99%